Positive effect of protozoa as starter diets for early stage of Asian seabass larvae - Mukai, Yukinori; S. H., Mohd Shahidin; Mohammad Noor, Normawaty; S., Mohd Idris; S., Mustafa (2020)
Seed production of marine finfish in Malaysia is still facing problem about live feed of starter diets. Currently, we use S or SS type rotifers, which have sizes from 100 to 200μm. Early stage larvae of some marine finfish species select feeds less than 100 μm. Protozoa is a collective term of aquatic microorganism that has been identified to be suitable live feed, as their body sizes are less than 100μm. The objective of this experiment is to compare the survival rates of Asian seabass larvae using four types of live feeds, rotifer, protozoa, one of protozoa E. encysticus, and mixed (rotifer, protozoa, and E. encysticus) were used. Protozoa showed positive effect for survival rates of Asian seabass larvae.